2006
DOI: 10.1103/physreva.73.022346
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocality without inequality for almost all two-qubit entangled states based on Cabello’s nonlocality argument

Abstract: Here we deal with a nonlocality argument proposed by Cabello, which is more general than Hardy's nonlocality argument, but still maximally entangled states do not respond. However, for most of the other entangled states, maximum probability of success of this argument is more than that of the Hardy's argument.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 9 publications
1
43
0
Order By: Relevance
“…We showed that on applying the principle of Information causality this bound decreases from 0.5 to 0.20717 in both the cases, but could not reach their respective Quantum mechanical bounds. Interestingly, in quantum mechanics the maximum probability of success for the Cabello's case is not same as the Hardy's case [20]. Since the condition given by equation (11) of the present paper is a sufficient condition derived in [15] for the violating IC, the probability derived here are therefore, strictly, an upper bound on the maximum probabilities allowed in an IC-respecting no-signaling theory.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…We showed that on applying the principle of Information causality this bound decreases from 0.5 to 0.20717 in both the cases, but could not reach their respective Quantum mechanical bounds. Interestingly, in quantum mechanics the maximum probability of success for the Cabello's case is not same as the Hardy's case [20]. Since the condition given by equation (11) of the present paper is a sufficient condition derived in [15] for the violating IC, the probability derived here are therefore, strictly, an upper bound on the maximum probabilities allowed in an IC-respecting no-signaling theory.…”
Section: Resultsmentioning
confidence: 83%
“…Later, Cabello [19] has introduced a logical structure to prove Bell's theorem without inequality for three particles GHZ and W states and the argument is also applicable for two qubits [20,21]. Hardy's logical structure is a special case of Cabello's structure.…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, Kunkri et al [25] proved that the maximum probability of success in Cabello's argument for two twoqubits system is approximately 11%, which is larger than the original Hardy's success probability. Here, we show that the maximal bound of success probability of Cabello's case has also no advantage in higher-dimension quantum systems and it can be used to generate much more randomness compare to the original Hardy test.…”
Section: B Cabello Paradoxmentioning
confidence: 95%
“…Subsequently, in the literature generalizations [6] of the Hardy's argument appeared aiming at softening some of the correlations requested by the original argument. In fact, the authors of Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Now, one might wonder if a relation exists between the Hardy-like nonlocality conditions, as those mentioned in Refs. [1] and [6], and Bell-like inequalities [3,4]. The aim of this paper is precisely that of showing clearly how the just mentioned relations are nothing but particular instances of a violated Clauser-Horne inequality [4].…”
Section: Introductionmentioning
confidence: 99%